The collective blog as a portal to an affinity space: developing the hybrid classroom in a university course in Colombia - Lombana-Bermudez, Andres (2021)
The article presents a case study of a hybrid classroom experience in a university class of Social Communication in Colombia, in which an affinity space was built through the use of information and communication technologies (ICT). Using the theories of affinity space (Gee, 2003, 2005, 2017) and connected learning (Ito et al., 2013) and based on qualitative data collected during four iterations of the class “Communication and Interactivity” (2019-2, 2020-1, 2020-2 and 2021-1), the case reflects on the process of building an affinity space and on the design and implementation of a collective blog as a tool for teaching and learning. By analyzing of the contents and interactions created in the affinity space, particularly in the blog, I inquire about the possibilities for innovation offered by designing environments that are production-centered, networked, and that have a shared purpose. The study results confirm that a collective blog is a useful tool for building affinity spaces, promoting connected learning, and developing hybrid classrooms.